The Myth of the ’Law-Free’ Paul Standing between Christians and Jews - Nanos, Mark (Studies in Christian-Jewish Relations, 2011)
Christians and Jews agree that the Apostle Paul did not observe Torah as a matter of faith, or in his daily life, except when he sought to evangelize among Jews who observed Torah. This perspective and the reasoning provided to explain it conceptualize the essential difference between Christianity and Judaism as revolving around Paul and his supposedly "Law-free Gospel," more so than around Jesus and his teachings. This understanding derives from the perception that Paul did not observe Jewish dietary norms, and that, moreover, he taught other Christ-followers not to observe them. This essay engages the primary texts on which this is based (Gal 2:11-15; 1 Cor 8—10; Rom 14—15) and finds that, contrary to the prevailing view, they show that Paul implicitly and even explicitly supported Jewish dietary norms among Christ-followers. The results challenge centuries of interpretation, with broad implications for Christian and Jewish portrayals of Paul and of the supposed foundations for differences that require and provide strategies of "othering" that continue to pose obstacles to progress in Christian-Jewish relations.